2018
DOI: 10.1111/jfd.12920
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence on prevention of infection by the ectoparasitic protozoans Ichthyobodo salmonis and Trichodina truttae in juvenile chum salmon using ultraviolet disinfection of rearing water

Abstract: In northern Japan, juvenile chum salmon Oncorhynchus keta (Walbaum) are released from hatcheries to enhance the fishery resource. Infections with ectoparasitic protozoans, particularly the flagellate Ichthyobodo salmonis and the ciliate Trichodina truttae, occasionally cause severe mortality among hatchery‐reared juveniles. This study examined the susceptibility of the two parasites to wide‐ranging UV irradiation (experiment 1) and then investigated whether UV disinfection of the rearing water using a commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In vitro tests revealed that the minimum lethal UV doses for protomonts and tomonts were 2.0 × 10 6 and 3.5 × 10 6 μWs cm −2 , respectively. These doses were higher than the minimum lethal UV doses for Ichthyobodo salmonis 39 (9.6 × 10 5 μWs cm −2 ), Trichodina truttae 39 (8.4 × 10 5 μWs cm −2 ) and theronts of C. irritans 3 (2.88 × 10 5 μWs cm −2 ). These differences are attributed to species differences or different sensitivities to UV at each stage of the pathogen life cycle 3,38 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In vitro tests revealed that the minimum lethal UV doses for protomonts and tomonts were 2.0 × 10 6 and 3.5 × 10 6 μWs cm −2 , respectively. These doses were higher than the minimum lethal UV doses for Ichthyobodo salmonis 39 (9.6 × 10 5 μWs cm −2 ), Trichodina truttae 39 (8.4 × 10 5 μWs cm −2 ) and theronts of C. irritans 3 (2.88 × 10 5 μWs cm −2 ). These differences are attributed to species differences or different sensitivities to UV at each stage of the pathogen life cycle 3,38 .…”
Section: Discussionmentioning
confidence: 76%
“…The UV lamp is a commonly used device whose sterilization effect increases with the increase in UV dose. 3,38,39 The rate of killing for sea lice eggs was 5% at a UV dose of 0.008 J cm −2 , but increased to 95% when the UV dose was 0.09 J cm −2 . 38 Similarly, a UV dose of 2.69 × 10 5 μWs cm −2 did not kill theronts of C. irritans but the UV dose became lethal it was above 2.88 × 10 5 μWs cm −2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation